Hypoxia conditioning for load-compromised athletes: a narrative review exploring potential applications in injury and disability management - Yeung, W.-C. V.; Kwok, V.; Ihsan, M.; Girard, O. (Sports Medicine, 2025)
Background: Load-compromised athletes are individuals with acute or chronic injuries or disabilities that hinder their ability to perform at peak levels. Hypoxia conditioning is broadly categorized into systemic (i.e., exposure to terrestrial or normobaric hypoxia) or localized (ischemic preconditioning, blood flow restriction training) approaches and could represent a viable option to increase exercise tolerance of load-compromised athletes. Purpose: This review evaluates the potential of hypoxia conditioning as a training and rehabilitation tool for load-compromised athletes. It explores its applications across various rehabilitation stages and key para-athlete sub-groups including spinal cord injury, limb deficiency, and cerebral palsy. Evidence: Passive hypoxia conditioning strategies using external limb compression help maintain musculoskeletal function during early rehabilitation stages involving immobilization or minimal loading. As rehabilitation progresses, both systemic and localized hypoxia conditioning (i.e., blood flow restricted exercise) effectively modulates external load while maintaining adequate (internal) physiological strain to induce beneficial cardiometabolic or musculoskeletal adaptations with lower mechanical stress. Para-athletes facing challenges such as biomechanical limitations, reduced active muscle mass, or muscle weakness can benefit from hypoxia conditioning`s capacity to enhance muscle aerobic function, promote muscle strength and hypertrophy, and improve cardiorespiratory performance at lower mechanical loads. Conclusion: Hypoxia conditioning emerges as a promising intervention to potentially overcome the physical and physiological challenges faced by load-compromised athletes. By addressing their specific limitations, hypoxia conditioning can optimize rehabilitation and training outcomes. Future research is essential to refine hypoxia conditioning protocols and tailor them to maximize individual adaptability and performance across diverse load-compromised athlete populations.